2014
DOI: 10.1099/vir.0.069765-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of new aphid lethal paralysis virus (ALPV) isolates suggests evolution of two ALPV species

Abstract: Aphid lethal paralysis virus (ALPV; family Dicistroviridae) was first isolated from the bird cherry-oat aphid, Rhopalosiphum padi. ALPV-like virus sequences have been reported from many insects and insect predators. We identified a new isolate of ALPV (ALPV-AP) from the pea aphid, Acyrthosiphon pisum, and a new isolate (ALPV-DvV) from western corn rootworm, Diabrotica virgifera virgifera. ALPV-AP has an ssRNA genome of 9940 nt. Based on phylogenetic analysis, ALPV-AP was closely related to ALPV-AM, an ALPV iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…Sequence data suggested that three viruses, ALPV [20], RhPV, and ApGIV2, were present in the laboratory colony of A. glycines . In order to isolate A. glycines infected only by ApGlV2, we established single-family aphid colonies.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence data suggested that three viruses, ALPV [20], RhPV, and ApGIV2, were present in the laboratory colony of A. glycines . In order to isolate A. glycines infected only by ApGlV2, we established single-family aphid colonies.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence comparison of ALPV isolates (Table 2) suggests two separate species of ALPV. ALPV-AP and ALPV-AM group separately from other ALPV isolates [5].…”
Section: Dicistroviridaementioning
confidence: 99%
“…Aphid lethal paralysis virus (ALPV, Genus: Cripavirus) was first isolated from the bird cherry-oat aphid, Rhopalosiphum padi [21]. Recently, ALPV isolates associated with the honey bee [11,12] and western corn rootworm [5] were discovered. In addition, ALPV sequences were identified in RNA from bat fecal samples [8], although these sequences were most probably derived from viruses infecting insects that were ingested by the bat.…”
Section: Dicistroviridaementioning
confidence: 99%
See 1 more Smart Citation
“…However, several tentative viruses have been identified that show sequence similarity to the members of the genus Iflavirus yet are classified as unassigned viruses at this time (12,16,21,70,71). Previous phylogenetic analysis suggested that iflaviruses have evolved from different origins since the viruses infecting insects from the same order do not form a single clade (3,17).…”
mentioning
confidence: 99%